The dynamics of sowing areas and productivity of spring barley in the Russian Federation - G. A. Filenko; T. I. Firsova; Yu. G. Skvortsova; E. G. Filippov (Зерновое хозяйство России, 2018)
Spring barley is one of the most early-maturing and adaptable crops with a great diversity of forms and varieties occupying a significant part of sowing areas in RF. The high adaptive ability of barley to various growing conditions causes its wide distribution throughout the country. The article considers economic value of the crop and gives the examples of its use in the industrial processing. Such essential indexes as a dynamics of sowing areas and productivity of spring barley in the Russian Federation for the period of 2010-2016, as well the tendencies of their increase and decrease have been analyzed in the work. The major sowing areas of spring barley in the Russian Federation are concentrated in four federal districts (Prevolzhsky, Tsentralny (Central), Sibirsky (Siberian) and Yuzhny (Southern)) with about 87.8% annual sowing areas occupied by spring barley. The Orenburgsky region ranks first among the regions and areas of Russian in the amount of spring barley sowing areas in 2016. The analysis of spring barley productivity in 2010-2016 showed that the Prevolzhsky, Tsentralny (Central), Sibirsky (Siberian) and Yuzhny (Southern) federal districts were the leading ones due to the average productivity of spring barley 2.13-2.56 t/ha. The special attention in the article has been devoted to the analysis of the results obtained in the Southern federal district and in the Rostov region. The article considers the expediency of increasing the production of spring barley due to the expansion of sown areas occupied by this culture, both in the Russian Federation and in other federal districts.